Synthesis and characterization of a new hydrogen bonded side chain liquid crystal block copolymer and investigation of electrical properties - Korkmaz, Burak; Ozerol, Esma Ahlatcioglu; Bozdogan, Aysegl Celik; Okutan, Mustafa; Senkal, Bahire Filiz; Gursel, Yesim Hepuzer (WALTER DE GRUYTER GMBH, 2017)
A new PEG-containing liquid crystalline side chain block copolymer HBC-PEG550 was prepared from poly(ethylene glycol)-b-poly(2-(diethylamino) ethyl methacrylate copolymer (BC-PEG550) and 8-(4-cyanobiphenyl-4'-oxy) octan-1-ol (LC8) by molecular self-assembly processes via hydrogen bond formation between amine group of HBC-PEG550 and hydroxyl group of the LC8. The formation of H bond was confirmed by using FTIR spectroscopy. The liquid crystalline behavior of the HBC-PEG550 was investigated by differential scanning calorimeter (DSC) and polarized optical microscopy. Dielectric properties of HBC-PEG550 and HBC-PEG550 has been studied by impedance spectroscopy. Real and imaginary parts of complex dielectric constant, impedance, and energy loss tangent factor for HBC-PEG550 and HBC-PEG550 have been characterized in the frequency range of 100 Hz-15 MHz.
Keywords: hydrogen bonding; liquid crystalline polymers; POC-16; polyethylene glycol; MESOGENIC ACIDS; POLYMERS; DESIGN; Chemistry